Displacement of a Broken Dental Injection Needle Into the Perivertebral Space. Issue 5 (July 2017) - Sahin, Bayram; Yildirimturk, Senem; Sirin, Yigit; Basaran, Bora
Abstract : Abstract: Dental injection needle breakage is an uncommon problem in dental practice. Displacement of the broken fragment into anatomical spaces is, on the other hand, a serious complication that occurs most commonly during inferior alveolar nerve blocks as a result of material wear, incorrect application of the anesthesia technique, or sudden movement of the patient during injection. Further complications such as infection, trismus, and nerve paralysis may exacerbate the condition and, if not treated adequately, life-threatening conditions may develop over time as the fragment dislodges deeper in soft tissues. Clinical symptoms of the patient, as well as the findings gathered from detailed physical examination and radiographic evaluation, are important factors to consider before performing an exploratory surgery. Removal of a broken needle may be troublesome due to its proximity to vital anatomic structures. Multislice computed tomography is a reliable imaging modality that provides accurate information to pinpoint the exact location of the needle fragment. This report describes a case of needle breakage occurred during inferior alveolar nerve block which was performed to extract a third molar tooth and the migration of the broken fragment from the right mandibular ramus area into the perivertebral space, with special emphasis on the surgical retrieval technique with multiplanar computed tomography imaging guidance.